2014
DOI: 10.1128/aem.03463-13
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio coralliilyticus Strain OCN008 Is an Etiological Agent of Acute Montipora White Syndrome

Abstract: dIdentification of a pathogen is a critical first step in the epidemiology and subsequent management of a disease. A limited number of pathogens have been identified for diseases contributing to the global decline of coral populations. Here we describe Vibrio coralliilyticus strain OCN008, which induces acute Montipora white syndrome (aMWS), a tissue loss disease responsible for substantial mortality of the coral Montipora capitata in Ka ne'ohe Bay, Hawai'i. OCN008 was grown in pure culture, recreated signs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
116
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(126 citation statements)
references
References 47 publications
3
116
1
1
Order By: Relevance
“…Vibrio bacteria have been associated with white band disease (40)(41)(42) and have been shown to cause WS-like disease signs in aquarium-based infection experiments (20,(22)(23)(24). In the current study, however, we found no significant difference in the relative abundance of sequences affiliated with Vibrio bacteria between health states.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Vibrio bacteria have been associated with white band disease (40)(41)(42) and have been shown to cause WS-like disease signs in aquarium-based infection experiments (20,(22)(23)(24). In the current study, however, we found no significant difference in the relative abundance of sequences affiliated with Vibrio bacteria between health states.…”
Section: Discussioncontrasting
confidence: 55%
“…Tissue loss associated with Indo-Pacific WSs has been attributed to a number of etiological agents, including Vibrio bacteria (20)(21)(22)(23)(24), apoptosis (25), ciliates (11,26), helminths (11), viruses (27), and intraspecific chimeric parasites (11,28), suggesting that distinct and potentially distinguishable forms of WSs exist. Based on logical deduction, we contend that the WS lesions observed in this study are not the result of apoptosis or infection by Vibrio bacteria, ciliates, fungi, cyanobacteria, or helminths, because of the low levels and inconsistent presence of these organisms at WS lesion fronts.…”
Section: Discussionmentioning
confidence: 99%
“…Although a direct link between V. coralliilyticus and widespread coral disease outbreaks has not been definitively established, this bacterium has been implicated in coral tissue loss diseases, collectively known as white syndromes (WS), at sites across the Indo-Pacific (Ben-Haim et al 2003;Sussman et al 2008;Ushijima et al 2014). Additionally, aquariumbased infection experiments have demonstrated the ability of V. coralliilyticus to cause WS-like disease signs in several Indo-Pacific coral species (Sussman et al 2008;Vidal-Dupiol et al 2011;Ushijima et al 2014).…”
mentioning
confidence: 99%
“…Although a direct link between V. coralliilyticus and widespread coral disease outbreaks has not been definitively established, this bacterium has been implicated in coral tissue loss diseases, collectively known as white syndromes (WS), at sites across the Indo-Pacific (Ben-Haim et al 2003;Sussman et al 2008;Ushijima et al 2014). Additionally, aquariumbased infection experiments have demonstrated the ability of V. coralliilyticus to cause WS-like disease signs in several Indo-Pacific coral species (Sussman et al 2008;Vidal-Dupiol et al 2011;Ushijima et al 2014). This potentially pathogenic bacterium is easy to culture, and several strains have been isolated from diseased corals that could be modified to allow specific visualization and tracking (Ben-Haim and Rosenberg 2002;Ben-Haim et al 2003;Thompson et al 2005;Sussman et al 2008;Vizcaino et al 2010;Ushijima et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation